Locoregional failures and their relation to radiation fields following stereotactic body radiotherapy boost for oropharyngeal squamous cell carcinoma. Issue 6 (12th January 2019) - Baker, Sarah; Verduijn, Gerda; Petit, Steven; Nuyttens, Joost J; Sewnaik, Aniel; van der Lugt, Aad; Heemsbergen, Wilma D.
Abstract: Background: To investigate the location of recurrences with respect to the radiation fields in oropharynx cancer after intensity‐modulated radiotherapy and stereotactic body radiotherapy (SBRT) boost. Methods: Local and regional recurrences were delineated on diagnostic scans which were rigidly coregistered with treatment planning scans, then classified based on the location of the center of mass (COM) as well as volumetrically. Results: In 195 patients, the 5‐year local and regional control were 90% and 93%, respectively. By COM, 76% of local recurrences were in‐field; 24% were out‐of‐field, significantly higher than 0%‐5% in the literature for conventional regimens ( P < 0.01). Regional recurrences (19 in 12 patients) were largely within unirradiated neck levels (47%) and electively irradiated regions (42%). Conclusions: The regimen with biological equivalent dose intensification provides excellent overall and in‐field local control. The highly conformal boost technique was, however, associated with increased out‐of‐field local failure.